The Influence of Religious Well Being on Family Resilience in Maintaining a Positive Outlook During The COVID-19 Pandemic - Yoyok Bekti Prasetyo; Faridi Faridi; Nur Lailatul Masruroh; Nur Melizza; Agung Dwi Laksono; Yazid Abdullah (Universitas Aisyah Pringsewu, 2023)
Objective: Resilience is a person's ability to solve problems or adapt positively despite difficulties. Spiritual well-being (SWB) is considered a positive thing to solve various problems and is used as an alternative for self-care during the covid pandemic. This study aimed to determine the effect of religious well-being on family resilience in maintaining a positive outlook during the COVID-19 pandemic. Methods: The research design used is descriptive with a cross-sectional approach. Respondents in this study were 243 villagers in East Java Province. The Spiritual Well-Being Scale (SWBS) and Family Resilience Assessment Scale (FRAS) questionnaires were used. Data analysis used binary logistic regression and multivariate logistic regression. Results: Religious Well-being affects family resilience in maintaining a positive outlook. Families with adequate religious well-being will have one time chance of having resilience in maintaining a positive outlook compared to families with inadequate religious well-being (OR: 1.081; 95% CI: 1.038 – 1.127). Conclusion: Family resilience in maintaining a positive outlook is strongly influenced by religious well-being factors. Strengthening the community with a religious approach is needed to support the family's line of defense against this pandemic condition.